Lectinas vegetais: de moléculas de defesa de plantas às suas diversas aplicações biotecnológicas - Oliveira, Jaqueline Franciele Caetano de (2018)
Lectins are proteins belonging to a diverse superfamily, which has as its main characteristic, the capacity to specifically and selectively recognize carbohydrates. They are present in a great variety of microorganisms, such as viruses, bacteria, fungi, plants, and animals. Due to its ability to recognize a large number of glycans, they behave as mediators in many biological processes, as in cell migration, immunologic defense and in bacterial, protozoan and viral infections. Among all, plant lectins are the most studied, showing structural heterogeneities, mainly on its carbohydrates binding sites, what grants several biological activities to these proteins, among them, the antimicrobial, insecticide, mitogenic, anti-tumoral and anti-inflammatory activities. On the last decades, a large number of studies have demonstrated the application of lectins as a potential biotechnological tool on diverse fields like on agriculture, being used at the genetic improvement of grains; on biochemistry, where it’s used at pre-purification of glycoproteins, and on the histochemistry, applied at the distinction between normal and tumoral cells. Nowadays, one of the researched applications is the potential of lectins as a carcinogenic agent, so as its uses on the discovery of biomarkers. The present study shows a brief history of the plant lectins, their functional characteristics, and structural, their biotechnological applications, such as in the biomarkers discovery, covering too, some of the techniques employed to this function, like the Lectin Affinity Chromatography (LAC), Lectin Microarrays and the Antibody-Lectin Sandwich Array.